Pelanggaran HAM di Sekolah - Rohyana Salmi; Rianta Malau; Anisa Siregar; Syahrial Syahrial (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This article discusses violations of Human Rights (HAM) in the school environment. The school environment must be a place that is safe, inclusive and respectful of individual rights. However, human rights violations continue to occur involving several parties. This article provides an overview of the forms of human rights violations that most often occur in schools as well as the factors that cause these violations and their consequences. In this article, we identify several forms of human rights violations that often occur in schools, including physical violence, verbal abuse, intimidation, sexual harassment, discrimination and inhuman punishment. This research aims to determine various types of human rights violations in schools and their prevention. This research uses qualitative methods that focus on in-depth observations and reviewing literature and case study reports regarding human rights violations in schools. The research results show that human rights violations in schools can take the form of physical violence, verbal abuse, threats, sexual harassment, discrimination and inhuman punishment.